Skin barrier repair can improve the related physiological indexes of mouse models of type 2 diabetes mellitus - Li YE; Si WEN; Zhen YI; Linshan WU; Xuesong XIAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To explore the role of skin barrier function repair in improving mouse models of type 2 diabetes mellitus. Methods BKS-Lepr-/- GPT mice were divided into the barrier repair group and the control group, and BKS-Lepr+/+GPT mice were set up as the wild type control group. The barrier repair group took the application of skin barrier repair agent as the intervention measure, and the skin barrier function indicators were detected by the barrier function detector. Results Compared with mice in the control group, the water content in the cuticle, the speed of water loss, the pH value of the epidermis, and TNF-α、IL-6 and spleen index of the mice in the repair group were effectively improved (P<0.05), blood glucose was effectively delayed at 17 and 26 weeks of age, and insulin sensitivity index was effectively improved at 26 weeks of age (P<0.05); Compared with mice in the wild type control group, the water content of the cuticle was slightly lower, and the transcutaneous water loss was consistent with the epidermal pH, TNF-α of mice in the repair group. There were significant differences of IL-6, spleen index, blood glucose and insulin sensitivity index (P<0.01). Conclusion Skin barrier function repair can effectively improve immune homeostasis, and delay elevating of blood glucose and aggravation of insulin sensitivity index in diabetes mice.